Identification of anti-HIV macrocyclic daphnane orthoesters from Wikstroemia ligustrina by LC–MS analysis and phytochemical investigation - Otsuki, Kouharu; Zhang, Mi; Kikuchi, Takashi; Tsuji, Minami; Tejima, Miyuko; Bai, Zi-Song; Zhou, Di; Huang, Li; Chen, Chin-Ho; Lee, Kuo-Hsiung; Li, Ning; Koike, Kazuo; et al. (Journal of natural medicines, 2021)
Macrocyclic daphnane orthoesters (MDOs) have attracted significant research interest for the drug discovery to cure HIV infection based on the “Shock and Kill” strategy. In the present study, the first chemical study on Wikstroemia ligustrina (Thymelaeaceae) was carried out by LC–MS analysis and phytochemical investigation. Nine daphnane diterpenoids ( 1 − 9 ) including seven MDOs were detected by LC–MS analysis. Further phytochemical investigation resulted in the isolation and structural elucidation of five daphnanes ( 1 , 2 , 5 , 8 , and 9 ) with potent anti-HIV activity. Taking the isolated MDO ( 1 ) as a model compound, the MS/MS fragmentation pathway was also elucidated.